2009
DOI: 10.1017/s1368980009005023
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of food and nutrient intake estimates using a semi-quantitative FFQ in Australian adults

Abstract: Objective: To assess the reproducibility of a 135-item self-administered semiquantitative FFQ. Design: Control subjects who had previously completed an FFQ relating to usual dietary intake in a nationwide case-control study of cancer between November 2003 and April 2004 were randomly selected, re-contacted, and invited to complete the same FFQ a second time approximately one year later (between January and April 2005). Agreement between the two FFQ was compared using weighted kappa statistics and intraclass c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 25 publications
1
53
3
1
Order By: Relevance
“…There have been reports on sex/gender differences in reproducibility of FFQs in adults and self-reporting children and adolescents; however, in general, results are not conclusive. 7,8,17,18,23 One possible explanation of our results might be the fact that we used proxy reports on diet. When parents and other proxies report on the children's intakes, it is possible that the sex of the proxy is more important than the sex of the child.…”
Section: Discussionmentioning
confidence: 95%
“…There have been reports on sex/gender differences in reproducibility of FFQs in adults and self-reporting children and adolescents; however, in general, results are not conclusive. 7,8,17,18,23 One possible explanation of our results might be the fact that we used proxy reports on diet. When parents and other proxies report on the children's intakes, it is possible that the sex of the proxy is more important than the sex of the child.…”
Section: Discussionmentioning
confidence: 95%
“…First, number of odorants in the SDOIT may limit the ability to detect small decrements in odor identification or to distinguish hyposmia (partial loss of smell) from anosmia (complete loss of smell) [31,32]. Second, dietary intake was self-reported using FFQs which are known to underestimate energy intake and overestimate fruit, vegetable, and dairy intakes [33]. Nevertheless, a comprehensive assessment of the whole diet is less subject to measurement error than is the assessment of energy intake alone [34], and several TDS components used in this study were designed to account for misreporting [23,35].…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, then our estimates would be biased downwards and, consequently, the true estimates might be higher than those we observed thereby strengthening our conclusions that folate intake is not associated with reduced risk of ovarian cancer, and high folic acid intake might be associated with an increased risk among women who consume 10 g or more alcohol per day. Measurement error is always an issue, but to minimise this we used a dietary questionnaire that has been validated for (Marks et al, 2006a, b) and has been shown to be reproducible in (Ibiebele et al, 2009) the Australian population. Furthermore, among 185 control women, serum folate levels were correlated with total dietary folate equivalents as measured by our FFQ (r ¼ 0.40, Po0.0001).…”
Section: Discussionmentioning
confidence: 99%